Implementation of Health Protocols during the Covid-19 Pandemic - Suci Artanti; Sapto Haryatmo (Jurnal Kesehatan, 2022)
Corona virus is a virus that can cause disease in the respiratory tract, which can develop to be more severe and can cause death. This virus quickly spreaded so that in March 2020 Covid-19 was declared as a pandemic. The implementation of health protocols is one of the most effective ways to reduce the spread of the corona virus. This study aims to find out how respondents get information about health protocols and how the implementation of health protocols is carried out by the community during the covid-19 pandemic. This research is a quantitative research with descriptive method. A total of 266 respondents were obtained by purposive sampling technique. The results of the study indicate that social media is the most appropriate means to be used as a medium to disseminate health protocols to young people and adolescents. In addition, the implementation of health protocols is quite good for the community except in terms of limiting mobility, especially among teenagers. The role of parents, teachers and adults is needed to improve youth discipline in implementing health protocols. The implementation of health protocols such as wearing masks, washing hands, maintaining distance must be more strictly implemented if it is not possible to avoid crowds and limit social mobility.